Elevated Perioperative Transaminase Level Predicts Intrahepatic Recurrence in Hepatitis B-related Hepatocellular Carcinoma After Curative Hepatectomy - Cheung, Yue-Sun; Chan, Henry L.Y.; Wong, John; Lee, Kit-Fai; Poon, Terence C.W.; Wong, Nathalie; Lai, Paul B.S. (Asian journal of surgery, 2008)
We aimed to evaluate the role of elevated perioperative alanine aminotransferase (ALT) as a surrogate marker of hepatitis activity in determining the risk of recurrence and survival in hepatitis B-related hepatocellular carcinoma (HCC) after curative hepatectomy. A retrospective review of the hepatectomy database was performed and 142 patients were found who had hepatitis B-related HCC from January 2001 to March 2006. Their ALT levels preoperatively and 1 month, 3 months, and 6 months postoperatively were recorded. The risk factors for recurrence and prognostic factors of survival were analysed. An elevated perioperative ALT level ( p = 0.021), multiple tumour nodules in the resected specimen ( p < 0.001), and a tumour size greater than 5 cm ( p = 0.001) were significant independent risk factors for tumour recurrence. The latter two factors were also independent prognostic factors for overall survival and disease-free survival. An elevated ALT level was an independent prognostic factor for disease-free survival ( p = 0.025). An elevated perioperative ALT level, which reflects increased hepatitis activity, is an independent risk factor for intrahepatic recurrence of hepatitis B-related HCC. It is also associated with a poorer disease-free survival rate.